Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1161/circulationaha.116.023381
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Proteomics Reveals Interplay of Aggrecan and Aggrecanases in Vascular Remodeling of Stented Coronary Arteries

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(77 citation statements)
references
References 49 publications
2
74
1
Order By: Relevance
“…It has been demonstrated that the VSMCs play a fundamental role in the pathogenesis of vascular lesions, including lipid retention, ECM production, and plaque integrity maintenance [33,34]. Previous studies have reported that ADAMTS-5 and proteoglycans were expressed in human coronary arterial VSMCs [16]. Consistent with previous reports, doubleimmunofluorescence staining indicated that the VSMCs were the major source of ADAMTS-5 in human CAD atherosclerotic plaques.…”
Section: Variablessupporting
confidence: 83%
See 1 more Smart Citation
“…It has been demonstrated that the VSMCs play a fundamental role in the pathogenesis of vascular lesions, including lipid retention, ECM production, and plaque integrity maintenance [33,34]. Previous studies have reported that ADAMTS-5 and proteoglycans were expressed in human coronary arterial VSMCs [16]. Consistent with previous reports, doubleimmunofluorescence staining indicated that the VSMCs were the major source of ADAMTS-5 in human CAD atherosclerotic plaques.…”
Section: Variablessupporting
confidence: 83%
“…ADAMTS-5, known as aggrecanase-2, has the highest aggrecanase activity and contributes to vascular remodeling [16,17]. Suna et al reported that the expression level of ADAMTS-5 was markedly decreased in stent-induced vascular injury, associated with the accumulation of proteoglycans, notably aggrecan and versican [16]. In addition, decreased ADAMTS-5 expression was found in atherosclerosis of apolipoprotein E (ApoE) null mice, associated with the accumulation of aggrecan and versican [18].…”
Section: Introductionmentioning
confidence: 99%
“…As indicated above, TLRs play a crucial role in the early inflammatory triggers that initiate vein graft remodeling. Among the first mediators of inflammation in vein grafts are DAMPs such as aggrecan and heat shock proteins ( 135 , 136 ). Endogenous DAMPs activate TLRs that are expressed by cells in the vein graft wall such as endothelial cells and SMCs ( 1 , 73 , 137 ).…”
Section: Immune Modulationmentioning
confidence: 99%
“…With proteins executing the majority of cellular structural and functional roles 14 , proteome analytics obviates misinterpretation due to discrepancies between transcript and protein readouts arising from posttranscriptional processing and splicing, and differing mRNA versus corresponding protein isoform half-lives. Indeed, use of proteomicsbased assessment has proven increasingly valuable for comprehending cardiovascular biology in health and disease [15][16][17][18] .…”
Section: Introductionmentioning
confidence: 99%